SELF-ESTEEM AND READING COMPREHENSION:: A CORRELATIONAL STUDY OF TENTH GRADERS - Aisya Perdana Asmaja; Shynta Amalia; Hariana Amalia (Didascein : Journal of English Education, 2025)
Reading is emphasized as a crucial activity for personal development and academic achievement. Strong reading comprehension skills not only support students’ academic performance but also contribute to the development of critical thinking and the expansion of knowledge. Understanding the factors that influence reading comprehension, such as self-esteem, is essential and worth exploring, particularly in the context of secondary education, where foundational skills and cognitive growth play a significant role in learning outcomes. This study aimed to investigate the correlation between self-esteem and reading comprehension achievement among tenth-grade students at MA Patra Mandiri in Palembang. To analyze the correlation between students’ self-esteem and their reading comprehension achievement, a correlational research design was applied. The study involved nine classes of tenth-grade students, and a sample of 116 students was drawn using a convenience sampling technique. Data were collected using a ready-made self-esteem questionnaire adopted by Kartika (2023) and a reading comprehension test. The findings indicated that the correlation coefficient (r) was 0.125, which was lower than the critical value of the r-table (0.180). Based on these results, it can be concluded that there was a low but insignificant correlation between self-esteem and reading comprehension achievement of tenth-grade students at MA Patra Mandiri Palembang